Ferry Boat Injuries and Deaths in Pattaya, November 2013: Its’ Time for Thailand to Reclaim its Safe Hospitality - Thawillarp, Supharerk; Waiyanate, N; Chen, L; Akechalermkiat, S; Srichang ์N; Ritthidej, P (Outbreak, Surveillance, Investigation & Response (OSIR) Journal, 2014)
On 3 Nov 2013, the Bureau of Epidemiology was notified of a ferry boat accident in Pattaya, Chon Buri Province. At least six deaths and 16 severe injuries were reported. The investigation team conducted a descriptive study to describe potential risk factors associated with injury and death, and determine the effectiveness of interventions on injury prevention after the accident. All medical records related to injuries and deaths from four hospitals were reviewed and interviews were held with patients, crew, heath volunteers, rescuers and local authorities. The team also observed ferry boat transportation services. Medical records of 37 hospitalized injuries, including seven deaths, were reviewed. Of these, 59% were males, with median age of 32 years. Major causes of injury were muscle strain (35%), aspiration pneumonia (19%) and submersion (14%). Five out of seven fatalities used a buoyancy aid, with one victim’s buoyancy aid reported to be “riding up”, which led to drowning. Overcapacity of the boat and inappropriate wearing of buoyancy aids accounted for the injuries and deaths. A multi-sectorial approach, including collaboration with National Institute of Emergency Medicine, Marine Department and, Department of Disaster Prevention and Mitigation, was essential to resolve safety issues resulting from resource constrained public transportation services.